Kualitas Pelayanan Kesehatan di RSUD Kota Kupang (Deskripsi Terminologi Pelayanan Kesehatan Berbasis Sarana,SDM, dan Fasilitas di Rsud Kota Kupang) 2014 - Pius Weraman; Apris Adoe (Jurnal Inovasi Kebijakan, 2016)
Implementation of Hospital services still have opportunities to improve the quality of service and take advantage of its resources, both human resources and financial resources, or capital economically and effectively. To improve the quality of service is not just a technical problem and the task of the hospital, but also our duty as a community, hopefully with the good cooperation, the services of the institution will be better. The purpose of this research is to find out the customer satisfaction, related to the medical technical services, and administrative services at the General Hospital of the city of Kupang. This type of research is descriptive research, which aims to describe or explain the events that occurred urgent nowadays. With cross sectional approach, which is an approach where the measurements or observations were made at the same time. Samples in this study is a part of the population which have been determined in accordance with the inclusion criteria, i.e. Clients Kupang City Hospital, concierge service providers in the hospital. Frequency distribution table is used for data analysis. The results obtained are the various deficiencies in the hospital from various aspects, especially the infrastructure and human resources. Thus, it can be recommended that the provision of infrastructure and equipment are needed to support the services in Kupang city hospital.